2022
DOI: 10.1186/s40645-022-00473-8
|View full text |Cite
|
Sign up to set email alerts
|

Imaging crustal features and Moho depths through enhancements and inversion of gravity data from the Philippine island arc system

Abstract: The Philippine archipelago is a complex island arc system, where many regions still lack geopotential field studies. The high-resolution isostatic anomaly and free-air anomaly digital grids from the World Gravity Map (WGM) were processed and analyzed to present a general discussion of the Philippines’ gravity signatures and contribute to understanding its regional geology and tectonics. The isostatic anomaly map was continued upward to investigate the high-density ophiolitic basement rocks and low-gravity sedi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Many studies have demonstrated the usefulness of RAPS in estimating interface depth [ 28 , 29 ]. The relationship of power spectrum and the depth [ 30 ] is expressed as, where is the wavenumber and is the depth of the source.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have demonstrated the usefulness of RAPS in estimating interface depth [ 28 , 29 ]. The relationship of power spectrum and the depth [ 30 ] is expressed as, where is the wavenumber and is the depth of the source.…”
Section: Methodsmentioning
confidence: 99%
“…A N‐S trending area, where S6 is 2–3.5 s TWT deep, separates the two areas (Figure 11f). The maximum basement depth estimated by gravity inversions is 11 km (Casulla et al., 2022).…”
Section: Seismo‐stratigraphy Of the Nw Sulu Seamentioning
confidence: 99%